Some Geometric Properties of a Hyperbolic Univalent Function - Al-Azawee, Sabah S.; Alhily , Shatha S. (Iraqi Journal of Science, 2021)
In this paper, we analyze several aspects of a hyperbolic univalent function related to convexity properties, by assuming to be the univalent holomorphic function maps of the unit disk onto the hyperbolic convex region ( is an open connected subset of). This assumption leads to the coverage of some of the findings that are started by seeking a convex univalent function distortion property to provide an approximation of the inequality and confirm the form of the lower bound for . A further result was reached by combining the distortion and growth properties for increasing inequality . From the last result, we wanted to demonstrate the effect of the unit disk image on the condition of convexity estimation by proving the two inequalities of , and .